Peran Islamic Social Reporting Dalam Memoderasi Pengaruh Zakat Terhadap Kinerja Keuangan Bank Umum Syariah - Chidir, Gusli; Asnaini, Sri Wahyuni; Radita, Fatrilia Rasyi; Rahmawati, Yunita (IAHN Gde Pudja Mataram, 2025)
This research aims to determine the impact of Islamic Social Reporting on zakat on the financial performance of Sharia Commercial Banks in Indonesia. The population for this research is all BUS registered with the OJK until December 2024. In Indonesia, 12 sharia commercial banks were selected using purposive sampling techniques. Data processing uses the Eviews 12 application and is quantitative in nature. These findings indicate that although Islamic social reporting does not have a real impact on financial performance (ROA) in Islamic Commercial Banks, reporting on zakat funds has quite a large impact. In addition, the impact of zakat on financial performance (ROA) can be mitigated with Islamic social reporting functions